ANALISIS KORELASI RASIO KEUANGAN ( Rasio Likuiditas, Solvabilitas, Aktivitas, Dan Rentabilitas ) - Sari, Murni Mala; Yandri, Pitri (Balance : Jurnal Akuntansi dan Bisnis, 2019)
This study aims to analyze the relationship between financial ratios at PT SWA Indomedika Prima. PT SWA Indomedika Prima is a company engaged in the field of health services by managing a group practice clinic specialist to serve Outpatient and Medical check-ups in BNI's Big Office divisions, Regional offices and BNI Branches throughout Jabodetabek and Karawang, Serang and Credit Centers Middle and small and Non BNI. This study uses the Structual Equation Modeling (SEM) analysis method. This research was conducted to find out how the relationships that occur in financial ratios, whether there is a positive or negative relationship. The ratio used in this study is Current Ratio (CR), Quick Ratio (QR), Cash Ratio (CsR), Debt Ratio (DR), Debt to Equity (DER), Total Asset Turn Over (TATO), Working Capital Turn Over (WCT), Return on Assets (ROA), Return on Equity (ROE). This study uses financial statements of PT SWA Indomedika Prima for 8 (eight) years, namely the period 2010-2017. The results of testing this study will be discussed further in this article.